Factors Determining the Three-Year Dynamics of Lipid Metabolism Indicators in Residents of a Large Industrial Region of Siberia - D. P. Tsygankova; E. D. Bazdyrev; E. V. Indukaeva; A. S. Agienko; O. V. Nakhratova; G. V. Artamonova; O. L. Barbarash (Рациональная фармакотерапия в кардиологии, 2022)
Aim. To assess the contribution of traditional and socio-economic factors to the development and dynamics of dyslipidemia based on the results of an epidemiological study in a large region of Siberia.Material and methods. Clinical and epidemiological prospective study of the population 35-70 years old was carried out. At the basic stage, 1600 participants were examined, including 1124 women and 476 men, the prospective stage included 807 respondents (the response was 84.1%). A survey was carried out to find out the state of health (presence of diseases, taking medications), socio-economic status (level of education and income, marital status) and the presence of behavioral risk factors (tobacco and alcohol use).Results. The proportion of people with hypercholesterolemia increased 1.2 times, low LDL – 1.1 times, and hypertriglyceridemia and low HDL – 1.7 times. In persons with hypertriglyceridemia, the frequency of detected obesity and hypertension decreased by 7.9% and 4.6%, respectively (p = 0.046). Obesity was associated with an increased risk of developing hypercholesterolemia (OR = 1.49, CI: 1.0-2.2), hypertriglyceridemia (OR = 2.14, CI: 1.5-3.0), high LDL cholesterol (OR = 2.16, CI: 1.3-3.6) and low HDL cholesterol (OR = 2.07, CI: 1.5-2.9). The presence of hypertension - with an increased risk of developing hypertriglyceridemia (OR = 2.19, CI: 1.5-3.1) and low HDL (OR = 2.49, CI: 1.8-3.5). Among people with low HDL levels, the number of smokers and drinkers decreased (by 7.0% and 5.7%, respectively), as well as those with obesity by 8.6%. The prevalence of dyslipidemia increased in all socioeconomic groups.Conclusion. Over 3 years of follow-up, there was a statistically significant increase in the proportion of persons with dyslipidemia in all socio-economic groups. There was a significant decrease in such risk factors as obesity, hypertension, smoking, alcohol consumption and an increase in the number of respondents taking lipid-lowering therapy.